Spectral Analysis of Al Arc Discharge Plasma Generated in ZnO/DDDW Colloid - Mena L. Badran; Saba. J. Kadhem (Iraqi Journal of Physics)
This study aims to investigate the aluminum (Al) arc plasma parameters generated through the explosive strip technique. The research involves the measurement of key plasma characteristics such as plasma frequency (fp), Debye length, and Debye number. The electron temperature (Te) and electron density (ne) of the plasma were calculated utilizing the Boltzmann plot and Stark expansion method. Analysis of the optical emission spectrum revealed distinctive peaks corresponding to oxygen, Al, and zinc oxide (ZnO) within the plasma. The outcomes of the study demonstrated a noteworthy correlation between the applied current and the electron temperature and density. Specifically, as the current increases, both electron temperature and density increase. The electron temperature of the Al plasma increased from the range of 0.852 eV to 0.92404 eV, accompanied by a corresponding elevation in electron density from 13.1× 1017 cm-3 to 15.2× 1017 cm-3. Furthermore, the detonation of the Al strip within a ZnO suspension led to even more pronounced changes. In this case, the electron temperature surged from 0.92885 eV to 1.1012 eV, and the electron density experienced an increase from 37.7 × 1017 cm-3 to 44.7 × 1017 cm-3.